Nonlinear mechanical behavior of non-conservative of hinged-fixed FGM beams in thermal environment - LI Qinglu; YANG Fanzhuan; ZHANG Jinghua (Journal of Aeronautical Materials, 2019)
Nonlinear mechanical behaviors of functionally graded material (FGM) beams subjected to tangentially distributed loads in uniform and inhomogeneous heating fields were investigated. Based on the geometric nonlinear theory of extensible beams, the governing differential equations of functionally graded material beams under tangentially distributed loads in thermal environment were established. The nonlinear mechanical behavior of FGM beams composed of ceramic zirconia and titanium alloy was analyzed by using shooting method. The equilibrium paths and configurations of FGM beams subjected to tangentially distributed loads under different uniform and non-uniform heating conditions were given. The effects of uniform and inhomogeneous temperature rise and material gradient parameters on bending and post-buckling behavior of beams were discussed in detail. The results show that FGM beams have the bending behavior, whereas the beams with homogeneous materials exhibit post-buckling behavior in thermal environment, and the non-uniform heating has a great influence on the mechanical behavior of non-conservative beams.